Analysis Of Student Learning Difficulties On Number Pattern Material Reviewed From Student Learning Independence - Kintan Utari Rusmawati (Department of Mathematics Education University of Muhammadiyah Malang, 2021)
This study aims to analyze students' learning difficulties in the number pattern material based on their level of learning independence and to look for factors that cause students to have learning difficulties. The method used in this research is descriptive qualitative. The subjects of the study were students of class VIII D SMPIT Adzkia, totaling 3 people, selected based on their level of learning independence. The instruments in this study were a learning independence questionnaire and a test instrument consisting of 4 questions related to the number pattern material to analyze students' learning difficulties. The results showed that: 1) students with high learning independence did not experience learning difficulties, 2) students with learning independence were having learning difficulties in determining concepts, and relating concepts to material (principles), 3) students with low learning independence had learning difficulties. in determining concepts, linking concepts with material (principles), and converting verbal problems into mathematical language. Keywords: learning difficulties, number patterns, independent learning